El informe de la Comisión sobre Macroeconomía y Salud: su relevancia para los países de América Latina y el Caribe
The Commission on Macroeconomics and Health (CMH) was established by the Director-General of the World Health Organization (WHO) to evaluate the role of health in economic development. On 20 December 2001 the CMH submitted its report to the WHO Director-General. Entitled Macroeconomics and Health: Investing in Health for Economic Development, the CMH report affirms that in order to reduce poverty and achieve economic development, it is essential to improve the health of the poor; to accomplish this, it is necessary to expand the access that the poor have to essential health services. The Commission believes that more financial resources are needed, that the health expenditures of less-developed and low-income countries are insufficient for the challenges that these countries face, and that high-income countries must increase their financial assistance in order to help solve the main health problems of less-developed and low-income countries. This piece summarizes a report that was prepared by the Program on Public Policy and Health of the Division of Health and Human Development of the Pan American Health Organization (PAHO). The PAHO document analyzes the importance of the CMH report for the countries of Latin America and the Caribbean, focusing on some of the central arguments put forth in the CMH report as they relate to achieving better health conditions in the Americas. These arguments have been organized around three major themes in the CMH report: a) the relationships between health and economic growth, b) the principal health problems that affect the poor in low-income and low-middle-income countries, and c) the gap between the funding needed to address the principal problems that affect these countries and the actual spending levels.